ANALYSIS OF THE EFFECTIVENESS OF SOFTWARE TESTING TECHNOLOGIES FOR INFORMATION SYSTEMS - Бринза, Наталя; Лобанов, Кирило (SWorldJournal, 2026)
The purpose of this work is to analyze the effectiveness of software testing. Modern approaches to software testing are analyzed, and their advantages, limitations, and areas of practical application are identified. To conduct a computational experiment,